Mandibular reconstruction with fibula free flap: a comparative analysis of clinical outcomes of CAD/CAM-assisted surgery versus model-assisted conventional technique - C. Giraudi; Ylenia Gugliotta; F. Secco; A. Novaresio; M. Fasolis; G. Ramieri (Oral and Maxillofacial Surgery, 2026)
Abstract Objectives The aim of this study was to compare clinical and patient-reported outcomes of mandibular reconstruction with fibula free flap (FFF) performed using model-assisted conventional technique versus computer-aided design/computer-aided manufacturing (CAD/CAM) with virtual surgical planning (VSP). Materials and methods Patients who underwent microvascular mandibular reconstruction with FFF between January 2016 and December 2023 were retrospectively reviewed. Inclusion criteria were age ≥ 18 years, segmental mandibular resection, and a minimum follow-up of 12 months. Patients were divided into two groups: model-assisted conventional reconstruction (Group A) and CAD/CAM-assisted reconstruction with VSP (Group B). Demographic, pathological, and surgical variables were collected. Morphological and functional outcomes were assessed using validated instruments including the Katsuragi Scale, FACE-Q Aesthetics, EORTC QLQ-H&N43, MD Anderson Dysphagia Inventory (MDADI), and Speech Handicap Index (SHI). Results Thirty-two patients were included (11 in Group A, 21 in Group B). CAD/CAM-assisted reconstruction showed significantly better aesthetic outcomes according to both patient and surgeon evaluations with Katsuragi Scale ( p = 0.0001). FACE-Q Satisfaction with Surgical Outcome scores were significantly higher in Group B ( p = 0.02). Patients treated with CAD/CAM also reported significantly fewer self-reported speech-related disturbances according to the SHI ( p = 0.01). Other functional measures showed favourable trends for CAD/CAM reconstruction but did not reach statistical significance. Conclusions CAD/CAM-assisted reconstruction was associated with improved aesthetic outcomes, greater patient satisfaction, and better speech-related function compared with conventional techniques. Clinical relevance Digital surgical planning may improve the precision and predictability of mandibular reconstruction and was associated with better patient-reported outcomes, particularly in speech-related function.